Traditional musical instruments in present musical life of Lebu' Kulit in Sungai Asap, Sarawak - Chieng, Julia Chin Yee (2012)
The Lebu’ Kulit people refer to themselves as belonging to one of the different subgroups of Kenyah. In the past, they migrated from Usun Apau and settled in few places on Borneo Island. The community is now separated and dispersed in different locations in Sarawak, Malaysia and East Kalimantan, Indonesia. At present, there is only one Lebu’ Kulit village in Sarawak. Since the year 1999, they have been staying in Sungai Asap in the Belaga District of Kapit Division. Along the stream of migrations and historical happenings which can be traced back to the early twentieth century, the Lebu’ Kulit people in Sungai Asap experienced a series of events such as headhunting, Dutch governance in Kalimantan, conversion to Christianity, the formation of Malaysia, the Confrontation War in the year 1963, and resettlement to Sungai Asap by the Sarawak government due to the construction of Bakun dam. As there is a lack of information on the musical culture of the Lebu’ Kulit in Sungai Asap, this is the first study that intends to document and analyse their present musical life and the culture of the community particularly on their traditional musical instruments. Several fieldtrips were made to the village from December 2009 to July 2011, and data on music practices as well as their cultural background were collected through audiovisual recordings, interviews, interactions, and participant-observations in their activities. Analyses and reflections were derived via study of audiovisual recordings,music transcriptions, and information obtained from interviews and observations. The traditional musical instruments in the present musical life of the Lebu’Kulit in Sungai Asap includes udang kadung (xylophone), sampé’ daru’ (zither),sampé’ bup (lute), sampé’ ja’au (lute), selingut (transverse flute), kediré’ alo’ (mouth organ), and wing or iceh (vessel rattle). These instruments are playedmostly in heterogeneous ensemble to accompany dance, songs or as instrumental music entertainment. The tuning of these musical instruments is similar to the western diatonic major scale. The musicians’ common repertoire consists of the traditional Kenyah tune Det Diet, the local folksongLenggang Kangkung, various Christian hymns and Gurkha songs. The performing style of a tune is usually repetitive with variations in rhythmic structures, registers, embellishments and dynamic accents. The playing of traditional musical instruments of the Lebu’ Kulit is significantly influenced by their beliefs especially through changes in their religion, historical events, present social and economic context, and individual self-expression. It seems that the traditional instrumental music of the Lebu’ Kulit has been “restarted” in a new form and meaning around sixty years ago and has become “singularised”. Besides, the frequency of traditional musical instruments playing has reduced to functions and festive seasons. The repertoire in the traditional musical sphere consists mostly of imported materials, and of which are adopted and internalised, and areexpressed in their own creativity and skills.